2013
DOI: 10.3389/fpsyg.2013.00804
|View full text |Cite
|
Sign up to set email alerts
|

The influence of status on satisfaction with relative rewards

Abstract: This study investigates how induced relative status affects satisfaction with different relative payoffs. We find that participants with lower status are more satisfied with disadvantageous payoff inequalities than equal or higher status participants. In contrast, when receiving an advantageous payoff, status does not affect satisfaction. Our findings suggest that relative social status has important implications for the acceptance of income inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 43 publications
3
26
0
12
Order By: Relevance
“…These two main effects suggest that both self- and other-status affect responses to resource distribution and confirm past studies suggesting that social status affects the acceptance of monetary allocations (Ball et al, 2001; Albrecht et al, 2013; Hu et al, 2014, 2016). Experiment 1 showed that participants were more likely to accept low offers from high status proposers, and this effect was more robust for participants in the low self-status group than in high self-status group.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These two main effects suggest that both self- and other-status affect responses to resource distribution and confirm past studies suggesting that social status affects the acceptance of monetary allocations (Ball et al, 2001; Albrecht et al, 2013; Hu et al, 2014, 2016). Experiment 1 showed that participants were more likely to accept low offers from high status proposers, and this effect was more robust for participants in the low self-status group than in high self-status group.…”
Section: Discussionsupporting
confidence: 87%
“…In these types of procedures, researchers manipulate the social status of participants by having them complete a rank-inducing task (e.g., trivia quiz, Ball et al, 2001; Albrecht et al, 2013), after which they give the participants a relative rank on the measured dimension in comparison with other participants, which is often indicated using stars (Ball et al, 2001; Zink et al, 2008; Hu et al, 2014, 2016). The use of stars is effective in indicating social status given their pervasive use in online shopping websites, videogames, and the military.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings gained in economic experiments indicate that expectations of fairness in humans vary greatly in respect of their social status: Status apparently modifies the perception of what is fair or acceptable. In bargaining situations, individuals with lower status are more likely to accept being overreached by higher status individuals than vice versa (Ball et al, 2001; Hu et al, 2014, 2016) Low status individuals are also more satisfied with disadvantageous payoffs than individuals with higher status (Albrecht et al, 2013). Van Prooijen et al (2002) sum it up as follows: people perceive the outcome of an interaction to be fair if they think that they are entitled to that outcome, and social status can determine whether people perceive themselves as entitled to certain outcomes.…”
Section: Introductionmentioning
confidence: 99%